Young People’s Voice: The First Visiting Advocacy Project in Italian Residential Care for Children - Calcaterra, Valentina; Raineri, Maria Luisa (Socialinė teorija, empirija, politika ir praktika, 2017)
This article presents the research of the project Giving Young People a Voice: Advocacy in Children’s Homes, set up as a result of the interest of a nonprofit organization working with looked-after children, with an aim to improve advocacy as a listening process and to promote the participation of children that reside in children’s homes. The research focused on the implementation of a visiting advocacy project and the activities carried out by an independent advocate working in children’s homes. The children’s evaluation of the project was collected by two focus groups; interviews were conducted with social care workers and the manager of the organization. This research deals with the implementation of the first visiting advocacy project in the context of the Italian child protection system.